The social savvy entrepreneur: Lean start-up branding and social media for MSMEs - Helen Dian Fridayani; Muhamamd Eko Atmojo; Muhammad Lukman Hakim; Aldryan Bagaskara Mahendro (University of Merdeka Malang, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are integral to Indonesia's economy, facing diverse challenges during the pandemic. This paper addresses the hurdles encountered by MSMEs, emphasizing the imperative of bolstering their branding and digital marketing competencies for enduring resilience. Despite their significance, many MSMEs, notably those in rural regions like Karangrejek Village, lack the requisite skills and resources for effective digital platform utilization, necessitating comprehensive support initiatives. Pandemic-induced issues encompass capital constraints and product marketing dilemmas, particularly evident among Karangrejek Village MSMEs. Post-pandemic recovery demands intensified aid to facilitate comprehensive revival, crucial for fostering local economic potential and community welfare enhancement. To address these challenges, a sustainable community service initiative will be launched, focusing on augmenting MSMEs' branding and digital marketing capacities. The program aims to stimulate optimal economic growth, especially in the post-Covid-19 era. It encompasses training sessions on leveraging digital media for product branding, expanding market reach through product marketing strategies, mentorship in product packaging design, and harnessing social media platforms. Through this initiative, MSMEs can fortify their resilience and contribute significantly to the community's economic prosperity.